2017
DOI: 10.1186/s12931-017-0555-4
|View full text |Cite
|
Sign up to set email alerts
|

Protein antigen of bird-related hypersensitivity pneumonitis in pigeon serum and dropping

Abstract: BackgroundAvian antigen is a common cause of hypersensitivity pneumonitis (HP). Inhalation challenge with pigeon serum and pigeon dropping extract (PDE) elicits a hypersensitivity reaction in patients with bird-related hypersensitivity pneumonitis (BRHP), but the antigenic components in these materials have yet to be fully elucidated.MethodPigeon serum, pigeon intestine homogenates, and PDE were immunoblotted with serum samples from 8 patients with BRHP, 2 patients with summer-type HP, 2 patients with humidifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 29 publications
2
14
0
Order By: Relevance
“…IGLL1, for example, has previously been reported in the uterus in a microarray experiment [27]. This protein was found in the protein component of the deeper layers of the shell [28] and appears to be a major secreted protein responsible for pigeon fanciers lung [29], but other than the strong indication that it is an epithelial secreted protein and its function remains obscure.…”
Section: Discussionmentioning
confidence: 99%
“…IGLL1, for example, has previously been reported in the uterus in a microarray experiment [27]. This protein was found in the protein component of the deeper layers of the shell [28] and appears to be a major secreted protein responsible for pigeon fanciers lung [29], but other than the strong indication that it is an epithelial secreted protein and its function remains obscure.…”
Section: Discussionmentioning
confidence: 99%
“…6-129.6). The prediction rule derived from the six factors had a sensitivity of 86% (95% CI, [79][80][81][82][83][84][85][86][87][88][89][90][91][92] and a specificity of 86% (95% CI, [81][82][83][84][85][86][87][88][89][90] with an HP prevalence of 45%. The receiveroperating characteristic (ROC) curve was 0.93 (95% CI, 0.90-0.95).…”
Section: Summary Of the Evidencementioning
confidence: 99%
“…Presently, such preparations are not yet commercially available or representative of all potential causative antigens of individual HP cases (eg, farmer's lung). 76,89,90 Since the performance characteristics and interpretation of the serum antigen-specific antibody test are often sitespecific and influenced by the prevalence of HP in the population being tested (ie, predictive value), the clinician ordering serum antigen-specific antibody testing should understand the validity and reliability of the test and the population sample type and size used to determine its diagnostic performance characteristics.…”
Section: Antigen-specific Antibody Testingmentioning
confidence: 99%
“…The molecular weight of IgA in pigeons is 200‐220 kDa, and antigen‐antibody reactions were observed at 220 kDa 23,24 . Proteins at 50 kDa, 29‐32 kDa, 26 kDa, and 21 kDa in pigeon droppings are reportedly associated with disease onset 5,25‐27 . In this study, multiple bands were found in the serum of patients with bird‐related CHP at 37‐75 kDa.…”
Section: Discussionmentioning
confidence: 50%
“…23,24 Proteins at 50 kDa, 29-32 kDa, 26 kDa, and 21 kDa in pigeon droppings are reportedly associated with disease onset. 5,[25][26][27] In this study, multiple In this study, Western blotting was performed to investigate the presence or absence of antibodies to pigeon eggs. If there were no antibodies for pigeon eggs, the changes after the inhalation challenge test may be caused by inhalation stimuli rather than an allergic reaction.…”
Section: Discussionmentioning
confidence: 99%